Optimization of cerbera manghas biodiesel production using artificial neural networks integrated with ant colony optimization - Silitonga A.S.; Mahlia T.M.I.; Shamsuddin A.H.; Ong H.C.; Milano J.; Kusumo F.; Sebayang A.H.; Dharma S.; Ibrahim H.; Husin H.; Mofijur M.; Rahman S.M.A. (MDPI AG, 2023)
Ant colony optimization; Esters; Kinetic theory; Neural networks; Physicochemical properties; Transesterification; Artificial neural network models; Biodiesel production; Cerbera manghas oil; Experimental values; Kinetic study; Process parameters; Transesterification process; Trial and error; Biodiesel